ANALISIS KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN BERDASARKAN THEORY OF PLANNED BEHAVIOR - Pontoh, Irene; Kesek, Meilany; Takakobi, Regina Beatrix; Sonu, Sri Sunarni; Wenur, Gebriany Pirade (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
This study aims to explore the factors that affect the level of taxpayer compliance in South Tondano District, Minahasa Regency, with a special focus on the influence of tax sanctions and fines on tax compliance behavior. Using a qualitative approach, this study collected data through in-depth interviews with taxpayers, government officials, as well as observations on the socialization and tax administration system in the area. The results show that the main factors affecting tax compliance include lack of understanding of tax regulations and the application of sanctions, low transparency in the management of tax funds, and uncertainty in tax administration procedures. In addition, taxpayers' attitudes towards the obligation to pay taxes, the influence of social norms in the surrounding environment, and the control of behavior felt by taxpayers also contribute significantly to their compliance. Despite the awareness of the importance of taxes for regional development, distrust of the management of tax funds and a complicated administrative system is a major obstacle. This study also found that to increase compliance, a more effective socialization strategy, increased transparency in the use of tax funds, and more consistent and firm enforcement of sanctions are needed. Based on these findings, it is recommended that local governments increase the use of digital technology for socialization, simplify tax procedures, and strengthen supervision and law enforcement systems to achieve optimal tax revenue targets and support sustainable regional development